Growth Evaluation of Red Tilapia (Oreochromis spp) Under Different Cycles of Fasting And Re-Feeding - Adam Robisalmi (BERITA BIOLOGI, 2022)
Feed restriction through fasting is a widely recommended feed management strategy in aquaculture, where this strategy is believed to have a positive effect on fish growth performance. This study aims to evaluate the growth performance of red tilapia in various cycles of fasting and re-feeding. The activity was carried out at Research Institute Fish Breeding from August to November 2020  . The research method used was experimental with 5 treatments with 4 replications, namely control (fish were fed daily), then the fasting treatment was S7 (7 days of fasting), S14 (14 days of fasting), S21 (21 days of fasting) and S28 (28 fasting day) followed by refeeding until the end of maintenance. Maintenance was carried out for 90 days in a concrete tub measuring 2x1m3 with a stocking density of 28 fishes / unit. During the rearing period the fish were fed satiation three times a day. The results showed that there was a decrease in growth along with the increase of the fasting period, but there was a trend of increasing growth after re-feeding with over compensatory growth in treatment S7 and partial compensatory growth in treatments S14 and S21. Likewise, the value of the condition factor and the hepatosomatic index during the fasting period decreased, but after feeding, the values were not different from those of fish fed continuously.